2017
DOI: 10.1371/journal.pone.0177593
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols and IUGR pregnancies: Maternal hydroxytyrosol supplementation improves prenatal and early-postnatal growth and metabolism of the offspring

Abstract: Hydroxytyrosol is a polyphenol with antioxidant, metabolism-regulatory, anti-inflammatory and immuno-modulatory properties. The present study aimed to determine whether supplementing the maternal diet with hydroxytyrosol during pregnancy can improve pre- and early post-natal developmental patterns and metabolic traits of the offspring. Experiment was performed in Iberian sows fed a restricted diet in order to increase the risk of IUGR. Ten sows were treated daily with 1.5 mg of hydroxytyrosol per kg of feed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 45 publications
8
42
3
Order By: Relevance
“…In fact, mean birth-weight of smallest and largest piglets and the range of within-litter weights were similar between controls and treated litters. The decrease in mean birth-weight found in the present study differs from the results obtained after maternal supplementation with only hydroxytyrosol [ 5 ]. In such study, mean birth-weight was increased whilst the incidence of LBW piglets was decreased.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In fact, mean birth-weight of smallest and largest piglets and the range of within-litter weights were similar between controls and treated litters. The decrease in mean birth-weight found in the present study differs from the results obtained after maternal supplementation with only hydroxytyrosol [ 5 ]. In such study, mean birth-weight was increased whilst the incidence of LBW piglets was decreased.…”
Section: Discussioncontrasting
confidence: 99%
“…Hydroxytyrosol is a polyphenol present in olive leaves and fruits with even higher antioxidant capacity than vitamin E [ 2 ]. Maternal supplementation during pregnancy improves oxidative and metabolic status of IUGR fetuses [ 3 , 4 ] and therefore incidence of LBW neonates and postnatal development of piglets [ 5 , 6 ]. Specifically, hydroxytyrosol diminishes lipid peroxidation and increases the fetal availability of omega-3 and omega-6 polyunsaturated fatty acids (n3 and n6 PUFAs) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results highlight the need for further studies on causes and significance of these effects, which are not specific of sheep. In this sense, studies in a different species, the pig, have shown that maternal supplementation with antioxidant compounds (polyphenols in this case), improves antioxidant status of the fetuses [30] and body weight of the neonates [31]. Afterwards, developmental patterns were positively affected by maternal supplementation independently of birth weight since, comparing individuals with similar weight at birth and weaning, piglets from supplemented sows reached higher average daily weight gain and, therefore, higher body weight and corpulence than their control counterparts [32].…”
Section: Discussionmentioning
confidence: 99%
“…In Wistar rats, HT supplementation (7.5 mg·kg −1 , twice a week, for 30 days) induced elevated TAG and lipid concentrations in cardiac muscle (Faine et al, ). Concerning non‐murine models, HT supplementation (1.5‐mg HT·kg −1 ·day −1 ), from Day 35 to delivery, resulted in raised TAG in the offspring of Iberian sows with diet‐induced risk of intrauterine growth restriction, compared to controls (Vazquez‐Gomez et al, ). In humans, the few available studies reported no effects on the lipid profile after HT consumption.…”
Section: Pharmacological and Nutraceutical Properties Of Htmentioning
confidence: 99%